Platformization of Academic Work in a COVID-19 Reality: Experiences of Foreign Language Faculty in Research-Intensive Universities in the United States - Sadowska, Iwona Beata (Trinity College Dublin. School of Education. Discipline of Education, 2023)
Despite research on how the coronavirus pandemic has changed work generally, a paucity of studies exists on the impact of the pandemic on academic work. One study suggests that remote, hybrid, and educational platform-mediated teaching in higher education is here to stay, but there is more to learn from the pandemic. Using intersectional feminist approaches and drawing on 12 semi-structured interviews, this study is the first to qualitatively address the gap in this learning. The study intentionally focused on an overlooked cohort of the United States professoriate. The study asks: How has a COVID-19 reality (and resultant rapid digitalization of teaching), as perceived by foreign language faculty among both cis and transgender women in research-intensive universities in the United States, shaped their working experiences? And, what role did gender, employment status, race, ethnicity, and age play intersectionally in shaping their COVID academic work? The findings of this study show a lack of vocabulary for the problems identified by the participants that point to a rise of self-surveillance, a decreased autonomy in edtech-dependent, home-workplace-collapsed spaces, and a doubling of "emotional labor" at home and at work to compensate for the reconfiguration of workspaces. To address this lack of vocabulary, the study coins the neologism of the platformization of academic work and analyzes four ways in which this platformization is transforming the academy and academics' lives. (1.) There was an increase in edtech-enhanced gendered and disciplinary temporal expectations and worktime. (2.) There was an increase in challenges relating to academic women's autonomy in the new reality, new gendered and technology-driven space demands, and struggles with new forms of domestic patriarchy and the right to workspace. (3.) There was an increase in struggles of faculty members to manage a professional body, strained by the increased demands from students for emotional support and by efforts to create an inclusive and conducive learning environment in an uneven digital space. (4.) In response to platformization, there was a birth of everyday leaders among women with insecure employment who intentionally led with compassion and empathy from places with little authority. These findings highlight the diversity of working experiences and the innovative strategies adopted by the women faculty interviewed to create inclusive learning environments in virtual spaces for students while navigating new, gendered, technology-driven work demands.
APPROVED
Keywords: feminist theory; digital edtech; work from home; intersectionality; higher education; pandemic; COVID-19; remote learning; digital education platforms